The Requirement of the National Democratic project in Iraq post Daesh Terrorist Group Stage - عمران أ.م.د.عمر جمعة (مجلة العلوم السياسية, 2020)
This study aims at re-transmit the spirit of the national democratic project of Iraq post of the chaos left by the Daesh terrorist group stage(The Islamic State of Iraq and Syria, ISIS) , Which controlled large parts of Iraq, and had an adverse effect on the political scene in Iraq, inspired everyone that there are deficiencies in the political, economic, religious and ethnic structure of the Iraqi people in non-response to democratic thought.The researcher relied on the hypothesis that " the requirements of building a democratic project are based on the need to provide the requirements ranging from two interrelated aspects, like the institutional aspect and the aspect that related to the general and necessary requirements for the establishment of democracy in society, in which the principles of majority rule, the rule of law, authority concentration on the principles of the people’s rule , and the rights of individuals guaranteed". This study utilized systematic analysis approach, historical approach,and the inductive approach undertaking the research. Government reports, statutes and laws were likewise hotspots for essential information in this review. Optional information was fundamentally from scholastic works, for example, books, diary articles, and theses. The results revealed that the model of building democratic Iraqi society post-ISIS needs primarily the government integrated system that includes principles, institutions and mechanisms that control the process of identifying options, making public decisions and the circulation of power periodically, In addition to balancing between rights and duties which can considered as the one of the main characteristic of democracy in order to achieve and developing security and stability in Iraq .